2008
DOI: 10.1016/j.brainres.2008.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive behavioral responses to chemical, thermal and mechanical stimulation after unilateral, intrastriatal administration of 6-hydroxydopamine

Abstract: The basal ganglia are involved not only with motor processes such as posture, pre-movement planning and movement initiation, but also with the processing and modulation of nociceptive somatosensory information. In the current studies, unilateral, intrastriatal 6-hydroxydopamine (6-OHDA) was used to investigate how dopamine depletion alters nociceptive behavioral responses to chemical, thermal and mechanical stimulation in rats. Compared to control rats injected with intrastriatal saline, rats depleted of dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 68 publications
5
24
2
1
Order By: Relevance
“…Since the direct dopaminergic projection from VTA exerts an inhibitory effect on electrical responses in the prefrontal cortex to mechanical noxious stimulation (Sogabe et al, 2013), the ascending dopaminergic projections should be considered to forward the future experiments. Previous studies have shown the effects of dopamine depletion during adulthood on nociceptive responses (Saade´et al, 1997;Takeda et al, 2005;Tassorelli et al, 2007;Chudler and Lu, 2008); however, these results were not always consistent with those of the present study. Decreased latency of withdrawal responses to mechanical and/or thermal stimuli has been observed in the hemi-Parkinson rat model (Takeda et al, 2005;Chudler and Lu, 2008), as also has the hyperalgesic response to a formalin injection (Tassorelli et al, 2007;Chudler and Lu, 2008).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Since the direct dopaminergic projection from VTA exerts an inhibitory effect on electrical responses in the prefrontal cortex to mechanical noxious stimulation (Sogabe et al, 2013), the ascending dopaminergic projections should be considered to forward the future experiments. Previous studies have shown the effects of dopamine depletion during adulthood on nociceptive responses (Saade´et al, 1997;Takeda et al, 2005;Tassorelli et al, 2007;Chudler and Lu, 2008); however, these results were not always consistent with those of the present study. Decreased latency of withdrawal responses to mechanical and/or thermal stimuli has been observed in the hemi-Parkinson rat model (Takeda et al, 2005;Chudler and Lu, 2008), as also has the hyperalgesic response to a formalin injection (Tassorelli et al, 2007;Chudler and Lu, 2008).…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have shown the effects of dopamine depletion during adulthood on nociceptive responses (Saade´et al, 1997;Takeda et al, 2005;Tassorelli et al, 2007;Chudler and Lu, 2008); however, these results were not always consistent with those of the present study. Decreased latency of withdrawal responses to mechanical and/or thermal stimuli has been observed in the hemi-Parkinson rat model (Takeda et al, 2005;Chudler and Lu, 2008), as also has the hyperalgesic response to a formalin injection (Tassorelli et al, 2007;Chudler and Lu, 2008). The discrepancy between the results of the present and previous studies is attributable to the anatomical extent (unilateral or bilateral lesion in the dopaminergic neural system) and developmental period (adulthood or neonatal) of dopamine depletion.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In one experiment rats were injected unilaterally with 5 μg of 6-OHDA into the STR and examined for changes in nociceptive behavior. Results revealed a hyperalgesic response to chemical stimulation of the face, and mechanical and thermal stimulation of the hind paws over the course of three weeks, with a severe loss of TH-ir neurons in the SNpc in the lesioned rats (Chudler and Lu, 2008). A unique method was used to by Gravotta et al (2011) to analyze circadian rhythm alterations in the 6-OHDA exposed rat.…”
Section: The Non-motor Features Of Toxin-induced Parkinsonismmentioning
confidence: 99%
“…In animal studies, microinjections of DA into the ACC reduced autotomy scores in a sciatic neurotomy model [15]. Behavioral in vivo studies of pain have demonstrated that DA depletion induces significant changes in thresholds for noxious stimuli [16,17]. Six-hydroxydopamine (6-OHDA) lesions in the VTA induced hyperalgesia in acute and chronic pain models [18].…”
Section: Introductionmentioning
confidence: 99%